Pengaruh Sistem Pembayaran Digital QRIS Terhadap Penjualan Pada Unit Usaha Kopma Store 1 Koperasi Mahasiswa “Almamater”Universitas Negeri Makassar - A.Alwansyah; Chalid Imran Musa; Muhammad Ilham Wardana Haeruddin; Siti Hasbiah; Nurul Fadillah (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to determine the effect of implementing the QRIS digital payment system on sales in the kopma store 1 business unit of the Alma Mater Student Cooperative of Makassar State University. The respondents in this study were as many as 100 consumers of Kopma Store 1 Makassar State University who made transactions using digital QRIS. This type of research uses a type of quantitative research with purposive sampling techniques as sampling techniques using certain considerations in accordance with the desired criteria to be able to determine the number of samples to be studied. In the sense that the sample taken is consumers who use the QRIS digital payment system. The data collection used are questionnaires, observations and documentation. The analysis method in this study uses instrument tests (validity tests, reliability tests), classical assumption tests (normality tests, heteroscadacity tests, linearity tests), hypothesis tests (determination coefficient tests, and t tests. The results of this study show that the QRIS digital payment system has a positive and significant effect on sales at the Kopma Store 1 Business Union of the Student Cooperative